Analisis Self Assessment Report dalam Rangka Penerapan Good Corporate Governance Pada PT. Gudang Garam, Tbk. Tahun 2020 - Farliza Atna Ayu Susanto; Caroline Yoshe Kolondam; Muhammad Sholikhul Huda; Iftah Nahdyatul Fatimah; Susi Handayani (JEMAP, 2023)
In this article, it is discussed about the Self-Assessment Report. The purpose of this article is the implementation of Corporate Governance implemented by PT. Gudang Garam, Tbk in 2020 in accordance with the results of the SAR analysis. The results of the SAR is also expected to be able to predict the development of PT Gudang Garam, Tbk. The author used  descriptive quantitative research method. The approaches of the research are the comparative approach and the literature approach. The SAR results showed a decrease in sales due to the Covid-19 pandemic which caused the gross profit margin to fall from 20.6 % to 15.2 %. The future results certainly depend on the Corporate Governance that is carried out.  The SAR analysis is very good so it can be ensured that the company has good development in the future.